Lightweight Low‐Frequency Sound‐Absorbing Composites of Graphene Network Reinforced by Honeycomb Structure. Issue 16 (27th July 2021) - Xu, Fan; Zhang, Siying; Wang, Guigen; Zhao, Daqiang; Feng, Junwei; Wang, Baolin; He, Xiaodong
Abstract: Efficient, facile, lightweight, and low‐frequency sound‐absorbing materials are in great demand for noise elimination and insulation. However, the applications of some candidate materials are limited by their large space, mass, or unsatisfactory sound‐absorption performance especially in low‐frequency sound‐wave region. Graphene network structure can be promising sound‐absorbing materials due to ultrahigh porosity, ultralight weight, and excellent intrinsic properties. Conventionally, allowing for poor mechanical strength, such graphene materials are needed to be reinforced by polymer, metal, or ceramic. Here, a novel strategy of graphene network reinforced by honeycomb structure is proposed, in which graphene is used as a sound absorber, and meanwhile flexible aramid honeycomb is introduced to enhance the graphene composite. In this work, the compressive strength of graphene network structure is improved 1000 times by the flexible aramid honeycomb, and meanwhile the density is only increased 2.5 times. Moreover, the sound‐absorption coefficient of graphene network is about 0.9 at 700 Hz for the thickness of 30 mm. Further, the sound‐absorption coefficient is above 0.9 in the frequency range of >1000 Hz. Therefore, the graphene composite is expected to be saving space and weight for the engineering design of sound absorbers in low‐frequency regions. Abstract : A novel large‐scale in‐plane, load‐bearing, and sound‐absorbing composite is prepared. Excitingly, this graphene network–aramid honeycomb structure (GN–AHS) has excellent sound‐absorption performance in low‐frequency region with thinner thickness and lower density. Additionally, GN–AHS has good ability of bending and anticompression, and it has potential application in wearable products and buildings.